Development and quality evaluation of low fat functional paneer - Kavya Kuttan; K. Radha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted to utilize skim milk for the preparation of low fat paneer, a value added product. Low fat paneer was prepared by using whey protein concentrate (WPC) and inulin as fat replacers. Full fat control paneer (C1) was prepared from buffalomilk standardized to 5 per cent fat and 9 per cent SNF. Skim milk control paneer (C2) was prepared from skim milk standardized to 0.3 per cent fat and 9 per cent SNF. WPC was incorporated at 0.25 (T1) and 0.5 per cent levels (T2). Inulin was used at the level of 1.5 (T1)and 2 per cent (T2) for the preparation of low fat paneer. The prepared paneer samples were evaluated for physico-chemical, microbiological and organoleptic qualities. Incorporation of WPC had significantly increased the yield as well as moisture content of low fat paneer. Inulin at 2 per cent level had increased the yield of low fat paneer. Both WPC and inulin had improved the sensory acceptability of low fat paneer prepared from skim milk.